Diurnal, seasonal, and annual trends in tropospheric CO in Southwest London during 2000–2015: Wind sector analysis and comparisons with urban and remote sites. (March 2018) - Hernández-Paniagua, Iván Y.; Lowry, David; Clemitshaw, Kevin C.; Palmer, Paul I.; Fisher, Rebecca E.; France, James L.; Mendoza, Alberto; O'Doherty, Simon; Forster, Grant; Lanoisellé, M.; Nisbet, Euan G.
Abstract: Ambient carbon monoxide (CO) and meteorological parameters measured at the Egham (EGH) semi-rural site in SW London during 2000–2015 have permitted wind sector analysis of diurnal and seasonal cycles, and interpretation of long-term trends. CO daily amplitudes are used as a proxy for anthropogenic emissions. At EGH, morning and evening peaks in CO arise from the dominant contribution of road transport sources. Smaller amplitudes are observed during weekends than weekdays due to lower combustion emissions, and for mornings compared to evenings due to the timing of the development and break-up of the nocturnal inversion layer or planetary boundary layer (PBL). A wavelet transform revealed that the dominant mode of CO variability is the annual cycle, with apparent winter maxima likely due to increased CO emissions from domestic heating with summer minima ascribed to enhanced dispersion and dilution during the annual maximum of PBL mixing heights. Over the last two decades, both mitigation measures to reduce CO emissions and also a major switch to diesel cars, have accompanied a change at EGH from the dominance of local diurnal sources to a site measuring close to Atlantic background levels in summer months. CO observed in the S and SW wind sectors has declined by 4.7 and 5.9 ppb yr −1 respectively. The EGH CO record shows the highest levels in the early 2000s, with levels in E and calm winds comparable to those recorded at background stations in Greater London. However, since 2012, levels in S-SW sector have become more comparable with Mace Head background except during rush-hour periods. Marked declines in CO are observed during 2000–2008 for the NE, E, SE (London) and calm wind sectors, with the smallest declines observed for the S, SW and W (background) sectors. For the majority of wind sectors, the decline in CO is less noticeable since 2008, with an apparent stabilisation for NE, E and SE after 2009. The EGH CO data record exhibits a similar but slower exponential decay, but from a much lower starting concentration, than do CO data recorded at selected monitoring sites in urban areas in SE England. CO/CO2 residuals determined using hourly averaged datain the diurnal cycle demonstrate a clear decline in CO from 2000 to 2015 during daily periods of increased vehicle traffic, which is consistent with a sustained reduction in CO emissions from the road transport sector. Graphical abstract: Highlights: CO data recorded at Egham (EGH) in Southwest London during 2000–2015 were analysed. CO varies on time scales ranging from minutes to inter-annual and annual cycles. CO declined at EGH more slowly than in Central London, but from a much lower starting point. The largest decline rates were observed for the calm and Eastern wind sectors. Assessment of CO/CO2 residuals confirmed a decline in CO during periods of increased vehicle traffic from 2000 to 2015.